Incidence and clinical management of oral human papillomavirus infection in men: a series of key short messages. Issue 8 (August 2014) - Videla, Sebastián; Darwich, Laila; Cañadas, MariPaz; Clotet, Bonaventura; Sirera, Guillem
Abstract : Oral human papillomavirus (HPV) infections are less prevalent than genital and anal infections. However, the incidence of oropharyngeal squamous cell carcinomas has increased significantly over the last 2 decades in several countries. At least 90% of these cancers are associated with oncogenic type HPV16. Oral HPV infections are notably more frequent in men than in women, and the incidence of HPV-positive oropharyngeal squamous cell carcinomas has increased, predominantly among mid-adult men. Nevertheless, little is known about the progression of oral HPV infection to cancer, and it remains unclear which medical interventions should be applied to modify the natural history of the disease. This narrative review aimed at non-experts in HPV infection provides an update on oral HPV infection and its clinical management in men. Furthermore, using the cervix as a reference anatomical site, the lessons learned from investigations on cervical HPV infection are also addressed.